Interactive effects of soil phosphorus and nitrogen availability on mycorrhiza-mediated nutrition in wheat - Margot Trinquier; Eric Lecloux; Bruno Patrick; Virginie Gasciolli; Claire Jouany; Christophe Roux; Benoit Lefebvre; Agnès Ardanuy (Plant and Soil, 2026)
Background and aims Arbuscular mycorrhizal fungi (AMF) play an essential role in plant nutrition in both natural and agro-ecosystems. However, how soil nutrient availability simultaneously regulates AMF diversity and contribution to plant nutrition, requires more attention. We hypothesised that the interaction between the availability of key soil macronutrients phosphorus (P) and nitrogen (N) regulates AMF contribution to wheat nutrition and that nutrient availability will simultaneously influence AMF community composition. Methods We tested this using a unique long-term P fertilisation trial, sampling wheat roots across two growing seasons. Expression of wheat mycorrhizal nutrient transporters was quantified by RT-qPCR and AMF communities were characterised by ITS2 metabarcoding. Complementary experiments under controlled conditions examined how the interaction between P and N regulates arbuscular mycorrhizal function in plant nutrition. Results Field-grown wheat showed campaign-specific effects of P fertilisation on AMF colonisation and nutrient transporter expression, which coincided with shifts in plant N status. Controlled experiments confirmed that colonisation depends on the limitation of either P or N, but that the regulation of peri-arbuscular phosphate, ammonium and nitrate transporters depended on the limiting nutrient. AMF communities also responded to soil P availability, with the genus Funneliformis consistently dominating under high P conditions. Conclusions Our findings demonstrate that P and N availability jointly shape root AMF communities and regulate their nutritive function in wheat. The combination of community profiling and mycorrhizal molecular markers provides a valuable approach for understanding the AMF contribution to plant nutrition across agroecosystems, and therefore can be used for optimising agroecological practices.

Clinical spectrum of ICU-acquired invasive pulmonary aspergillosis according to SARS-CoV2 infection: a multicenter prospective cohort study - Florian Reizine; Mattéo Mauget; Nicolas Massart; Yannick Fedun; Anaïs Machut; Charles-Hervé Vacheron; Anne Savey; Arnaud Friggeri; Alain Lepape; Melissa Abbes; Abdelkrim Abdelmalek; Francoise Adema; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Ubiquitination-mediated regulation of receptor-like kinases in symbiosis and immunity - David Landry; Benoit Lefebvre (Molecular Plant, 2024)

Analysis of the structure and function of the LYK cluster of Medicago truncatula A17 and R108 - Thi-Bich Luu; Noémie Carles; Louis Bouzou; Chrystel Gibelin-Viala; Céline Remblière; Virginie Gasciolli; Jean-Jacques Bono; Benoit Lefebvre; Nicolas Pauly; Julie Cullimore (Plant Science, 2023)

Rhizobium leguminosarum symbiovar viciae strains are natural wheat endophytes that can stimulate root development - Claudia Bartoli; Stéphane Boivin; Marta Marchetti; Carine Gris; Virginie Gasciolli; Mégane Gaston; Marie‐Christine Auriac; Frédéric Debellé; Ludovic Cottret; Aurélien Carlier; Catherine Masson‐Boivin; Marc Lepetit; et al. (Environmental Microbiology, 2022)
Although rhizobia that establish a nitrogen‐fixing symbiosis with legumes are also known to promote growth in non‐legumes, studies on rhizobial associations with wheat roots are scarce. We searched for Rhizobium leguminosarum symbiovar viciae ( Rlv ) strains naturally competent to endophytically colonize wheat roots. We isolated 20 strains from surface‐sterilized wheat roots and found a low diversity of Rlv compared to that observed in the Rlv species complex. We tested the ability of a subset of these Rlv for wheat root colonization when co‐inoculated with other Rlv . Only a few strains, including those isolated from wheat roots, and one strain isolated from pea nodules, were efficient in colonizing roots in co‐inoculation conditions, while all the strains tested in single strain inoculation conditions were found to colonize the surface and interior of roots. Furthermore, Rlv strains isolated from wheat roots were able to stimulate root development and early arbuscular mycorrhizal fungi colonization. These responses were strain and host genotype dependent. Our results suggest that wheat can be an alternative host for Rlv ; nevertheless, there is a strong competition between Rlv strains for wheat root colonization. In addition, we showed that Rlv are endophytic wheat root bacteria with potential ability to modify wheat development.

Comparative pharmacokinetics of difethialone stereoisomers in male and female rats and mice: development of an intra- and inter-species model to predict the suitable formulation mix - Antoine Rached; Virginie Lattard; Ambre Fafournoux; Hervé Caruel; Isabelle Fourel; Etienne Benoit; Sébastien Lefebvre (Archives of Toxicology, 2022)

Comparative biological properties of the four stereoisomers of difethialone, a second-generation anticoagulant rodenticide, in rats: development of a model allowing to choose the appropriate stereoisomeric ratio - Sébastien Lefebvre; Isabelle Fourel; Nolan Chatron; Hervé Caruel; Etienne Benoit; Virginie Lattard (Archives of Toxicology, 2020)

Expression and Secretion of Recombinant Outer-surface Protein A from the Lyme Disease Agent, Borrelia burgdorferi, in Nicotiana tabacum Suspension Cells - Catherine Navarre; Mélanie Delannoy; Benoit Lefebvre; Joseph Nader; Delphine Vanham; Marc Boutry (Transgenic Research, 2006)

Identification of a Nicotiana plumbaginifolia Plasma Membrane H+-ATPase Gene Expressed in the Pollen Tube - Benoit Lefebvre; Miguel Arango; Mohammed Oufattole; Jérôme Crouzet; Bénédicte Purnelle; Marc Boutry (Plant Molecular Biology, 2005)

Purification and Partial Amino Acid Sequence of Brevicin 27, a Bacteriocin Produced by Lactobacillus brevis SB27 - Valérie Benoit; Ahmed Lebrihi; Jean-Bernard Millière; Gérard Lefebvre (Current Microbiology, 1997)